2022
DOI: 10.1021/acsanm.2c00642
|View full text |Cite
|
Sign up to set email alerts
|

Bidentate Ligand-Induced Oriented Transformation of CsPbBr3 Perovskite Nanocrystals into Nanowires for X-ray Photodetectors

Abstract: Shape and dimensionality control by ligands is an efficient way to fabricate high-quality perovskite nanocrystals (NCs) with optoelectronic properties. Herein, to realize oriented transformations between different morphologies of CsPbBr 3 nanocrystals, we conceived of the use of defects and bidentate ligands to synergistically drive the reorientation of CsPbBr 3 nanocrystals into CsPbBr 3 nanowires (NWs). By employing aminocaproic acid as the bidentate ligand, CsPbBr 3 NWs were reconstructed from the CsPbBr 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…The recent reports on using zwitterionic molecules, e.g., lecithin, during the postsynthetic process shows enhanced surface adhesion along with precise size and shape control of perovskite NCs and may open a new direction for enhancing the stability of NCs colloids. While such zwitterionic molecules are promising for enhancement in the surface coupling, they still form an insulating layer around perovskite NCs and therefore may affect the charge transfer properties. In this regard, it is essential to comprehend the nature of surface coupling of such bidentate ligands on the NCs surface. Stronger surface coupling of these capping ligands may translate to the inherent lattice vibrations of perovskite NCs and may alter the optical properties of the coupled system. The dependence of size, shape, and composition of such coupling on the perovskite NCs also needs to be understood for tailoring their synthesis as well as their usage in optoelectronics.…”
mentioning
confidence: 99%
“…The recent reports on using zwitterionic molecules, e.g., lecithin, during the postsynthetic process shows enhanced surface adhesion along with precise size and shape control of perovskite NCs and may open a new direction for enhancing the stability of NCs colloids. While such zwitterionic molecules are promising for enhancement in the surface coupling, they still form an insulating layer around perovskite NCs and therefore may affect the charge transfer properties. In this regard, it is essential to comprehend the nature of surface coupling of such bidentate ligands on the NCs surface. Stronger surface coupling of these capping ligands may translate to the inherent lattice vibrations of perovskite NCs and may alter the optical properties of the coupled system. The dependence of size, shape, and composition of such coupling on the perovskite NCs also needs to be understood for tailoring their synthesis as well as their usage in optoelectronics.…”
mentioning
confidence: 99%
“…3 Liu et al studied an interesting phenomenon of ligand-induced transformation of CsPbBr 3 nanocrystals to nanowires for applications as X-ray photodetectors, where the photodetectors fabricated using the obtained CsPbBr 3 nanowires displayed enhanced photocurrents. 4 In another work, Beton and coauthors achieved submolecular resolution imaging based on P 3 HT:PCBM films, showing a promising application potential in organic photovoltaic devices. 5 McGrier et al measured the thermal conductivity of benzobisoxazole-linked nanoporous covalent organic frameworks, which are attractive for use as thermal management materials.…”
Section: Sustainabilitymentioning
confidence: 99%
“…Upon tuning, they found that the energy-transfer efficiency could be increased by 100% . Liu et al studied an interesting phenomenon of ligand-induced transformation of CsPbBr 3 nanocrystals to nanowires for applications as X-ray photodetectors, where the photodetectors fabricated using the obtained CsPbBr 3 nanowires displayed enhanced photocurrents . In another work, Beton and coauthors achieved submolecular resolution imaging based on P 3 HT:PCBM films, showing a promising application potential in organic photovoltaic devices .…”
Section: Nanosystems For Energy and Sustainabilitymentioning
confidence: 99%
“…It also has many applications in the field of analysis and testing, such as fluorescent probe 12 , ECL 13 , photoelectric chemistry 14 and so on. However, the stability of all inorganic perovskite nanoparticles is poor, especially in water, which greatly limits its practical application.…”
mentioning
confidence: 99%
“…7 At present, all inorganic perovskite nanocrystals (NCs) have been widely used in the preparation of high-efficiency solar cells, 8 light-emitting diodes, 9 lasers 10 and photodetectors. 11 They also have many applications in the field of analysis and testing, such as fluorescent probes, 12 ECL, 13 photoelectric chemistry 14 and so on. However, the stability of all inorganic perovskite nanoparticles is poor, especially in water, which greatly limits their practical application.…”
mentioning
confidence: 99%